Synthesis, physic and structural characterization of rare-earth oxynitrides REFeO3-xNx (RE=La, Pr, Nd, Sm) (2015)
This work studies the synthesis of the perovskite oxynitrides REFeO3-xNx (RE=La, Pr, Nd, Sm). For comparison purposes and as precursors in some of the synthesis reactions studied; their respective oxides, the orthoferrites REFeO3 (RE=La, Pr, Nd, Sm), have been synthetized by the self-combustion glycine-nitrate process. The oxides synthetized were characterized by XRD, Rietveld refinement, SEM and EDS in order to determine their purity and correct stoichiometry. These measurements establish that all the oxides synthetized crystallize as distorted perovskites with the orthorhombic space group pbnm and due to the synthesis method are highly porous materials with an open flakes morphology. Meanwhile the FT-IR measurements determined the presence of the bond Fe-O and the Mössbauer spectra of these oxides confirmed the location of iron in the structure in equivalent octahedral sites with oxidation state Fe+3. The thermal analysis results of the DSC and TGA curves showed a high content of mobile oxygen in the structure of the oxides. Moreover the magnetics curves of M vs H at 300K revealed antiferromagnetic behavior of the compounds, confirmed by the ZFC and FC curves, where also a weak ferromagnetism was observed at low temperatures. The electrical resistivities of the oxides were calculated by V vs I curves to be among the 0.2 and 4.9 MΩ·cm. Finally the polarization loops determined ferroelectric behavior for the four oxides with the greatest intensity found for the LaFeO3 composition. For the synthesis of the perovskite oxynitrides REFeO3-xNx (RE=La, Pr, Nd, Sm) different synthesis methods were evaluated. The thermal ammonolysis of the orthoferrites REFeO3 (RE=La, Pr, Nd, Sm) showed the reduction of iron in the structure to lower oxidation states promoting the formation of secondary oxides phases even at low temperatures and short reaction times. Moreover the nitriding tests by ammonia microwave-induced plasma (MIP) of the orthoferrites despite of the lower temperatures showed the reduction of iron in the structure too, indicating that in the same way that the ammonia reactivity increases due to the plasma state, the reactivity of the reduction potential of hydrogen also increases. Meanwhile solid state reactions under nitrogen atmosphere using oxide or nitrides precursors and urea as nitriding agent, result in the formation of the orthoferrites but any nitridation, which means the ammonia produced during the decomposition of urea is not efficient enough to promote the change in oxidation state of the iron for the formation of the oxynitride. Tests using urea and the orthoferrites as precursors in a high energy ball milling showed the formation of undesired carbonate phases due to the high energy collisions, indicating that the urea is not an adequate nitriding agent for this synthesis technique. Additionally a sol gel approximation to the synthesis of oxynitrides yielded mixtures of secondary oxides with high content of organic residues; where in order to obtain the perovskite structure calcinations under oxygen or air atmosphere around the 700 ºC had to be performed. In this way the orthoferrites were obtained but without nitridation. Finally as a complementary work presented as an annex in this book, from the transmission Mössbauer spectra recorded at room-temperature, the relative recoilless F-factor of the REFeO3 (RE =La, Pr, Nd, Sm) compounds were estimated. Applying a method based on the correct determination of the two subspectral areas present in a mixture of known amounts of the compound under study and a standard sample (α-Fe).